(untitled) (ModaPalavra e-periódico, 2021)
Currently, the uses and applications of textile products include those intended for domestic use (decorative textiles, furniture, etc.), passing through the wide field of clothing, on the one hand linked to the great social and cultural phenomena of fashion, and, on the other , to professional or sports clothing, including the specialized segment of technical fabrics, with its great influence on technological innovations, with an exponential growth in its applications and in its global technological demand. Within the textile activity, the knitting segment is one of the oldest, recovering its origin to the manual knitting process. Knitting technology is always evolving, and improvements in machine software systems and graphic design give technicians, designers and engineers more options for making technical fabrics. On the other hand, technological innovations in knitting machines are gradually making fashion more sustainable, through new forms of textile production that are more efficient, avoiding the waste of water, energy and raw materials in addition to eliminating pollution.